DIFFERENTIAL METHOD OF QUALITY CONTROL OF PHYSICO-MECHANICAL CHARACTERISTICS OF KNITTED FABRIC FOR BATHING SUIT - SLAVINSKA, Alla; MATIUKH, Serhii; MYTSA, Viktoriia (Herald of Khmelnytskyi National University. Technical sciences, 2022)
In order to ensure compliance of knitted fabrics to the established requirements of bathing suits, technical regulation of quality is considered. The normative regulation of technical control of knitted fabrics for the production of bathing suits is carried out. The option of normative documentation of examination of knitted fabrics for bathing suits is presented by a set of standards. The standards of the «Product Quality Indicators System» complex establish the nomenclature of mandatory and recommended indicators for assessing the level of product quality in various light industry industries. The choice of measurement methods and processing of measurement results is regulated by DSTU 2681-94. Analytically substantiated nomenclature of quality indicators by level of application: mandatory, additional, recommended. The differential method of estimating the quality of a knitted fabric has been experimentally tested. The selection of quality indicators for testing samples of knitted fabric is made taking into account the purpose and conditions of use of the product, analysis of consumer requirements and additional and recommended requirements. The differential method in the examination of group quality indicators is carried out by comparing the individual quality indicators of the evaluated canvas with the basic indicators of homogeneous products by purpose. The object of the research is knitted fabrics for bathing suits, made by double weaving of double-elastic bands (interlock) on two-font interlock circular knitting machines type I2108-28 of the Terrot class. According to the results of the experimental study of the recommended nomenclature of physical and mechanical quality indicators, the compliance of the knitted fabric of raw materials PE + PA with the requirements of the Standard for the manufacture of bathing suits was confirmed. The influence of classification features of knitted fabric on the variation of discontinuous elongation in the assessment of the elasticity of the material by quality indices is confirmed.
Keywords: knitted fabric; bathing suit; regulatory documentation; quality indicator; differential method